Imagineering cultural Vienna. On the semiotic regulation of Vienna's culture-led urban transformation. - Suitner, Johannes (transcript, 2015)
Die Arbeit analysiert den Einfluss dominanter Interpretationen von Kultur auf die Stadtentwicklung Wiens. Sie fragt, ob vereinfachte Konstrukte von Kultur als Instrumente der Machterhaltung und Legitimierung individueller Planungsinteressen fungieren können. Damit gibt sie Einblick in aktuelle kulturbasierte Transformationsprozesse der Stadt. Die Analyse offenbart mehrere Muster hegemonialer Praxis in Wiens kulturbasierter Stadtentwicklung und formuliert Empfehlungen an eine künftige kulturelle Planung, die sich eines erweiterten Kulturbegriffs annimmt.

Media discourses always consider Vienna as a "cultural city". This study shows how such a perception is skilfully shaped by political constructions of cultural imaginaries in and of the city. The book unveils how simplistic cognitive interpretations of culture not only define an unquestioned, reductionist idea of the city's cultural character - it also explains how these imaginaries influence the recent urban development practice in one of Europe's globalizing cities.
Keywords: Stadtplanung; Stadtentwicklung; Kulturpolitik; Stadtkultur; Strukturwandel; Marketing; Stadtmarketing; Transformation